2020
DOI: 10.3389/fonc.2020.00822
|View full text |Cite
|
Sign up to set email alerts
|

Arguments to Support a Viral Origin of Oral Squamous Cell Carcinoma in Non-Smoker and Non-Drinker Patients

Abstract: In some western countries, an increasing incidence of oral squamous cell carcinoma (OSCC) has been observed in non-smoker non-drinker patients (NSND), mostly in women with HPV-negative OSCC. In the context of the unknown etiology and mechanisms of tumorigenesis of OSCC in NSND, we discuss data supporting the hypothesis of a viral origin not related to HPV. OSCC from NSND are characterized by an antiviral DNA methylation and gene expression signature. Based on the similar increasing incidence of oral tongue SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Because viral genome integration has not been detected in non-smoking and non-drinking OSCC, a "hit and run" viral mechanism involving epigenome deregulation could therefore play a key role at early steps of oral carcinogenesis in this population of patients. [18] In our cohort, males OSCC were more likely to occur in buccal (38.4%) and tongue (35.3%) locations. The buccal mucosa is the most affected site in people with BQ chewing history due to frequent mucosa irritation.…”
Section: Discussionmentioning
confidence: 59%
“…Because viral genome integration has not been detected in non-smoking and non-drinking OSCC, a "hit and run" viral mechanism involving epigenome deregulation could therefore play a key role at early steps of oral carcinogenesis in this population of patients. [18] In our cohort, males OSCC were more likely to occur in buccal (38.4%) and tongue (35.3%) locations. The buccal mucosa is the most affected site in people with BQ chewing history due to frequent mucosa irritation.…”
Section: Discussionmentioning
confidence: 59%
“…Though the etiologic hypothesis of an oncovirus influence has been ascribed severally to NSND OCSCC tumorigenesis, 3,5,38 we found that specific investigations into viral detection and causation from the reviewed reports do not directly support this theory presently. Also, oral cancer predisposing factors, such as family history, poor oral hygiene, chronic periodontitis, and low educational attainment, were observed to take higher precedence in NSND OCSCC as associated factors.…”
Section: Discussionmentioning
confidence: 66%
“…The current hypothesis about carcinogenesis of oral SCC consists of an accumulation of genetic mutations in the oral epithelial cells, which may be favored by some risk factors such as excessive alcohol drinking and tobacco smoking [3,10]. However, there is an emerging population of patients with oral malignant tumors, but without exposure or with slight exposure to these two common risk factors, especially young and elderly women [10,11] [11]. In this case, there was no history of alcohol drinking and tobacco smoking.…”
Section: Figure6 Preoperative Histopathological Image Of Keratinizinmentioning
confidence: 99%